2003
DOI: 10.1002/j.2161-1912.2003.tb00532.x
|View full text |Cite
|
Sign up to set email alerts
|

Critical Issues in Cross‐Cultural Counseling Research: Case Example of an Ongoing Project

Abstract: Cross-cultural counseling practice is characterized by a proliferation of opinions without empirical substantiation. Most research in this area is based on survey or analog studies that do not address practice issues in terms of outcome or actual clinical process. The authors examine issues in crosscultural counseling and research, using illustrations from an ongoing study.El consejo intercultural se caracteriza por medio de la generacion de opiniones proliferas sin justificacion empirica. Muchos estudios en e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…Data for this report is taken from a naturalistic study of cross-cultural clinical practice, whose design and method have been reported elsewhere (Tsang et al 2003). Recognizing that the RCT (randomized control/clinical trial) design has problems related to both external and internal validity (Tsang et al 2003;Howard et al 1986Howard et al , 1990, we used a naturalistic design to examine what practitioners actually did in their day-to-day practice.…”
Section: Source Of Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Data for this report is taken from a naturalistic study of cross-cultural clinical practice, whose design and method have been reported elsewhere (Tsang et al 2003). Recognizing that the RCT (randomized control/clinical trial) design has problems related to both external and internal validity (Tsang et al 2003;Howard et al 1986Howard et al , 1990, we used a naturalistic design to examine what practitioners actually did in their day-to-day practice.…”
Section: Source Of Datamentioning
confidence: 99%
“…Data for this report is taken from a larger data pool in a naturalistic process-outcome study of cross-cultural clinical practice conducted at the University of Toronto (Tsang et al 2003). Based on multiple outcome measures, this study used outcome data to divide clients into positive and negative outcome cases.…”
mentioning
confidence: 99%
“…Finally, Safran and Muran's (2000b) techniques for rupture repair will be used to describe how cross-cultural issues can be repaired in the beginning phase of psychotherapy. Clinical vignettes were taken from the first author's practice experience in a New England state, as well as from a research project, ''An Integrated Outcome-Process Study of Cross Cultural Clinical Practice,'' (Tsang, Bogo, & George, 2003). This project was a naturalistic, exploratory study examining ''treatment as usual'' with therapeutic dyads at agencies in a Canadian urban area.…”
mentioning
confidence: 99%
“…From the perspective of anti-oppressive practice that emphasizes client empowerment, collaboration between therapist and client in determining goals and choosing intervention is considered critical to cultural competence (Hays, 2001;Lo & Fung, 2003;Sue & Sue, 2003;Tsang, 2003 Mental health is the capacity of the individual, the group and the environment to interact with one another in ways that promote subjective well-being, the optimal development and use of mental abilities (cognitive, affective and relational), the achievement of individual and collective goals consistent with justice and the attainment and preservation of conditions of fundamental equality. (Definition of mental health section)…”
Section: Significance Of the Practicummentioning
confidence: 99%
“…From the perspective of anti-oppressive practice that emphasizes client empowerment, collaboration between therapist and client in determining goals and choosing intervention is considered critical to cultural competence (Hays, 2001 ;Lo & Fung, 2003;Sue & Sue, 2003 ;Tsang, 2003). In contrast, aiming to understand cultural competency comprehensively, Lo and Fung (2003) examined its generic and specific aspects in psychotherapy and spelled out the following phases: pre-engagement, engagement, assessment/feedback, treatment/intervention, and closure/discharge.…”
Section: Cultural Competence and Healthcare For Ethnic Minoritiesmentioning
confidence: 99%